Atheism: History and Methodology - Minkevičius, Jokūbas (Problemos, 1983)
Confrontation between atheism and religion is conditioned by the concrete socio cultural and ideological process. The ancient atheism is a critical philosophical thought contrary to “the crowd’s opinion of gods” who were represented naturalistically and anthropomorphically. Atheism as the antipode to religion formed under the conditions of the European scientific revolution of Modern times and had an educational character. From the theoretical point of view, atheism is the product of the pre-Marxist methodology in explaining social phenomena. The dialectical-materialistic interpretation of his tory "withdraws" the atheistic denial of religion by its scientific investigation and by substantiation of socio-revolutionary solution of human problematics reflected in religion.